Aristotle’s thesis and the biconditional interpretation of conditional statements (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
Pfeifer holds that human beings do not interpret conditional statements as material conditionals, but as conditional events. To demonstrate it, he presents two experiments based on Aristotle´s thesis and, from the outcomes he obtained, he argues that it is obvious that his participants understood the conditional statements that were presented as conditional events. However, if we consider that conditional perfection phenomenon and conditional statements can be interpreted as biconditional statements, we can think of an alternative explanation for Pfeifer´s outcomes without admitting his thesis, namely, that conditional statements are interpreted as conditional events. In this paper, I try to prove that.
Keywords: Biconditional; conditional; conditional events; conditional perfection; material interpretation